Immunoreceptors on neutrophils - van Rees, Dieke J. (Semin Immunol, 2016)
Neutrophils play a critical role in the host defense against infection, and they are able to perform a variety of effector mechanisms for this purpose. However, there are also a number of pathological conditions, including autoimmunity and cancer, in which the activities of neutrophils can be harmful to the host. Thus the activities of neutrophils need to be tightly controlled. As in the case of other immune cells, many of the neutrophil effector functions are regulated by a series of immunoreceptors on the plasma membrane. Here, we review what is currently known about the functions of the various individual immunoreceptors and their signaling in neutrophils. While these immunoreceptors allow for the recognition of a diverse range of extracellular ligands, such as cell surface structures (like proteins, glycans and lipids) and extracellular matrix components, they commonly signal via conserved ITAM or ITIM motifs and their associated downstream pathways that depend on the phosphorylation of tyrosine residues in proteins and/or inositol lipids. This allows for a balanced homeostatic regulation of neutrophil effector functions. Given the number of available immunoreceptors and their fundamental importance for neutrophil behavior, it is perhaps not surprising that pathogens have evolved means to evade immune responses through some of these pathways. Inversely, some of these receptors evolved to specifically recognize these pathogens. Finally, some interactions mediated by immunoreceptors in neutrophils have been identified as promising targets for therapeutic intervention.